Influence of incomplete fusion on complete fusion at energies above the Coulomb barrier. (19th September 2017) - Shuaib, Mohd; Sharma, Vijay R; Yadav, Abhishek; Sharma, Manoj Kumar; Singh, Pushpendra P; Singh, Devendra P; Kumar, R; Singh, R P; Muralithar, S; Singh, B P; Prasad, R
Abstract: In the present work, excitation functions of several reaction residues in the system 19 F+ 169 Tm, populated via the complete and incomplete fusion processes, have been measured using off-line γ -ray spectroscopy. The analysis of excitation functions has been done within the framework of statistical model codepace4 . The excitation functions of residues populated via x n and p x n channels are found to be in good agreement with those estimated by the theoretical model code, which confirms the production of these residues solely via complete fusion process. However, a significant enhancement has been observed in the cross-sections of residues involving α -emitting channels as compared to the theoretical predictions. The observed enhancement in the cross-sections has been attributed to the incomplete fusion processes. In order to have a better insight into the onset and strength of incomplete fusion, the incomplete fusion strength function has been deduced. At present, there is no theoretical model available which can satisfactorily explain the incomplete fusion reaction data at energies ≈4–6 MeV/nucleon. In the present work, the influence of incomplete fusion on complete fusion in the 19 F+ 169 Tm system has also been studied. The measured cross-section data may be important for the development of reactor technology as well. It has been found that the incomplete fusion strength function strongly depends on the α -Q value of the projectile, which is found to be in good agreement with the existing literature data. The analysis strongly supports the projectile-dependent mass-asymmetry systematics. In order to study the influence of Coulomb effect ( Z P Z T ) on incomplete fusion, the deduced strength function for the present work is compared with the nearby projectile–target combinations. The incomplete fusion strength function is found to increase linearly with Z P Z T, indicating a strong influence of Coulomb effect in the incomplete fusion reactions.